Uma abordagem pragmalinguística de Lc 16,19-31: a centralidade dos empobrecidos no discípulado cristão - Souza, Tarlei Navarro Pádua (2021)
Jesus bore witness of love to the needy with words and actions. Luke, collecting the data of Tradition, sometimes attached such teaching through parables. The evangelist, therefore, wants the reader to understand that taking care of the poor is a fundamental requirement to the discipleship instituted by Jesus. The narrative of Lk 16:19-31, on its own gramatical construction, allows establishing a continuing relationship between Jesus’s teachings and the Scriptures, as far as solidarity is concerned. The pragmatics of the text refers to the ethical commitment in order to overcome the huge gap that separates those who accumulate wealth from the impoverished. The parable is an invitation to the readers-disciples of all times to bid together fraternal and egalitarian christian communities, not according to the pattern of Roman Empire’s power or current economic powers, but in the faithfulness to the Scripture’s teachings